Pola Sosialisasi Anak Dalam KeluargaTerhadap Perilaku Anak Di Desa SeberangPebenaan Kecamatan Keritang Kabupaten IndraGiri Hilir - ", Khairunnisah; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study was conducted to determine how patterns of socialization that happens ,religious values are socialized and constraints that affect the socialization process ofreligious values in the family in the village of Pebenaan Seberang Hilir SubdistrictKeritang Indragiri where every Friday prayers prayers and quantity fewer childrencompared with adults / parents , children often talk dirty and disrespectful to my friendsand parents.To find out how the patterns of socialization that occurs religious values aresocialized and the factors that influence the socialization process . Religious values inthe family in the village of Pebenaan Seberang Hilir Subdistrict Keritang Indragiri , theauthors conducted data collection by using the technique of guided interviews with theinformant , using parent and child informants throughout the Islamic religion andchildren who have aged 7-18 years. Purposive sampling 20 parents and 20 childreninformantsResults of research conducted showed that of authoritarian , democratic andpermissive , democratic pattern is a pattern that many families used to educate childrenin the assessment of religious values , religious values in this study covers theimplementation of the prayer 9 ( 45 % ) who do not discipline children while the parent- child discipline in praying as many as 12 ( 60 % ) of parents who discipline , readingAl - Quran ( Koran ) 14 ( 70 % ) of children who rarely Koran and here also seenparents who never Koran 10 ( 50 % ) parents who never Koran at all , fasting Ramadan13 ( 65 % ) children were less well in performing the fasting of Ramadan , while fastingRamadan parents in carrying out 17 ( 85 % ) included both parents in implementing theRamadan fasting . In keeping with the goal of planting religious values to children as ahandle and guidance in carrying out the teachings of Islam . When viewed from thepercentage of poor implementation of religious values also looks quite large , it istheoretically influenced by how socialization received in the socialization of children inkeluarga.faktor religious values , each child of the attitude of parents who are too loudand discipline that cause children to be passive communicates the difficulty of anyenvironmental influences 9 ( 45 % ) of children and adolescents who are less well in2social environment and advancement of technology 13 ( 65 % ) of children who oftena use tecnology very rapidly .Keywords :Patern of socialization family, religious values